Persepsi Remaja Putri Terhadap Jilbab Di Jorong Padang Mardani Nagari Manggopoh Utara Kecamatan Lubuk Basung Kabupaten Agam - Rahmadani, Suci (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
cover their genitals or do not use the hijab when meeting people who are not their mahram, QS Al-Nur verse 31. The background of the problems found, some teenagers do not use the hijab when leaving the house, and if there is any they use the hijab but the hijab used is short, or the hijab is long but the clothes are short or fit the body. In addition, some young women use the hijab only to follow fashion trends and also lack guidance from their parents. Therefore, the authors are interested in examining how young women perceive the hijab in Jorong Padang Mardani Nagari Manggopoh, Lubuk sub-district, Agam regency. This type of research uses survey research with a quantitative approach. The research location is in Jorong Padang Mardani Nagari Manggopoh, Lubuk Basung District, Agam Regency. because there the researchers found problems regarding the hijab in adolescents. The population is 233 young women in Jorong Padang Mardani, and the number of samples is 59 random samples. To collect data, the authors distributed questionnaires or questionnaires to young women. After the data is collected, data processing and analysis are carried out. Furthermore, the analysis of the research instrument was carried out. Based on the findings of data analysis, it can be concluded that the perception of young women regarding the law on the use of the headscarf is mostly (84.7%) giving mandatory answers, a small part (10.2%) answering sunnah, a small part (5.1%) answering permissible. Perceptions of young women regarding the time of wearing the hijab, a small part (14.7%) always use the hijab every time they leave the house, a small part (21.3%) often, a small part (24.9%) sometimes, a small part (24.9%) %) rarely, and a small proportion (14.2%) never use the hijab every time they leave the house. Young women's perception of the size of using the hijab, a small part (14.9%) always uses a long hijab size, a small part (24.8%) often, a small part (24.6%) sometimes, a small part (21.2%) ) rarely, and a small percentage (14.5%) never long hijab size. Adolescents' perception of the style or form of the hijab is a small part (19.1%) always the hijab style is straightened and slung over the shoulder, a small part (25.4%) often, a small part (25%) sometimes, a small part (21. 6%) rarely, and a small proportion (8.9%) never had the hijab straightened and slung over the shoulders.